Control Administrativo Del Departamento De Cobranzas De La Cooperativa De Ahorro Y Crédito San Antonio De La Sucursal Mata De Cacao - Yépez Mejía, Jaira Priscila (2019)
This case study seeks to monitor the Credit Portfolio of the SAN ANTONIO SAVINGS AND CREDIT COOPERATIVE, in the 2016-2017 period, the financial position and economic solvency of the Cooperative will be determined, using the different ratios and financial ratios. to the balances of the credit portfolios in the years to be analyzed, the analysis will be made to the policies of the credit portfolios maintained by the institution with the purpose of contributing with new suggestions that help to improve the daily activities carried out by the Cooperative. To arrive at these results, different methods, materials and techniques will be used, applying the use of the scientific, inductive, deductive, analytical, mathematical method, among others, and the description of the techniques of observation, interview, survey and bibliographic review. will allow to obtain useful information in the development of the present investigative work.